RIGHTS AND RESPONSIBILITIES OF JOURNALISTS IN NIGERIA: IMPLICATIONS FOR DEVELOPMENT - Anyanwu, B.J.C.; Awaeze, Collins; Etumnu, Emeka Williams (African Journal of Social and Behavioural Sciences, 2022)
The thrust of this paper is to review the rights and responsibilities of the journalists in Nigeria, in a bid to understand those rights and duties, know the responsibilities that are attached to the job of a journalist, examine whether those responsibilities are capable of forestalling the abuse of those rights and ultimately to examine how acquaintance and adherence to those rights and responsibilities helps the media to serve the social, political, economic and cultural systems, and bring about development in those areas in an emerging democracy and developing country such as Nigeria. The rationale is that journalists educate the public about social, political, economic and cultural events and issues and how they affect their lives. Doing so is a non-negotiable responsibility which the press, as an obligation, owes the masses and the political system that they serve, and that responsibility that comes with certain inalienable rights. The social responsibility theory served as the theoretical standpoint of this paper. The library research method was employed. The conclusion is that when journalists are well-grounded in those rights and responsibilities in Nigeria, they are better equipped, through their coverage, to contribute to social, political, economic and cultural developments in the country.